Born in the land of milk and honey: The impact of economic growth on individual wealth accumulation - Charlotte Bartels; Johannes König; Carsten Schröder (ZBW - Leibniz Information Centre for Economics, 2021)
Economic growth varies substantially across regions and over time. This paper shows that economic growth in a person's birth place is an important determinant for wealth in adulthood. We exploit a new dataset that oversamples wealthy individuals in Germany and includes information on birth district, current residence, individual wealth, gifts and inheritances and parental background. To identify the effect of economic growth on children's wealth we match the population of heirs to statistically equivalent non-heirs. We use regression analysis to determine the effect of regional economic growth on this inherited fraction of wealth. At an average level of GDP at birth, a one standard deviation higher per capita GDP growth at birth increases wealth in adulthood by roughly 130,000 Euro.
Keywords: D31; D64; O47; 330; wealth distribution; regional inequality; intergenerational transmission